Only in New York : an exploration of the world's most fascinating, frustrating and irrepressible city - Roberts, Sam, 1947- (Fordham University Press, 2019)
No one denies that New York City is unique--but what makes it sui generis? Sam Roberts, longtime city reporter, has puzzled over this in print and in his popular New York Times podcasts for years. In Only in New York, he writes about what makes New York tick and why things are the way they are in the greatest of all cities on earth. The forty essays in this book cover a variety of topics, including: Why do we have doormen? Is it noisier in the city or in the country? Are New Yorkers really as liberal as the rest of the country thinks they are? Why wasn't Manhattan's cross-town street grid oriented by the points of the compass? If a neighborhood loses its tony zipcode, does it lose its cachet? A winning and informative gift book for every fan of 'the city,' "Only in New York" is elegantly written and solidly reported.